Computational Approaches and Use of Chiroptical Probes in the Absolute Configuration Assignment to Natural Products by ECD Spectroscopy: A 1,2,3-Trihydroxy-p-menthane as a Case Study - Giulia Marsico; Umberto Calice; Patrizia Scafato; Sandra Belviso; Antonio Evidente; Stefano Superchi (Biomolecules, 2022)
In this study, the computational analysis of electronic circular dichroism (ECD) spectra and the employment of biphenyl chiroptical probes were compared in the absolute configuration assignment of (-)-1α,2α,3β-trihydroxy-p-menthane (1), taken as a representative example of a UV-transparent chiral natural product. The usefulness of chiroptical probes in the configurational assignments of natural products and their complementarity to the computational protocols is herein highlighted. The biphenyl probe approach proves to be straightforward, reliable, and suitable for conformationally mobile and ECD silent compounds, not treatable by computational analysis of chiroptical data.